Comparative Wood Anatomy of 20 Woody Plant Species in Northeastern Mexico and its Significance - Maiti, Ratikanta; Rodriguez, Humberto Gonzalez; Diaz, Jeff Christofher Gonzalez; Tijerina, HaydeeAlejandra Duenas; Flores, Arturo Allejandro Chavez; Kumari, Aruna; Sarkar, N. C. (International Journal of Bio-resource and Stress Management, 2023)
A study has been undertaken on wood anatomy of 20 woody species in northeast Mexico. There exists large variation among species in wood anatomical traits such as porosity, vessel diameter, its distribution, parenchyma, compactness of ground tissues and fibre cell characteristics. Most of the species have narrow vessels which help protection against cavitation. Most of the species are ring to semiring porous viz., Acacia amentacea, Acacia berlandieri, Acacia shaffneri, Acacia wrightii, Cordia boissieri, Helietta parviflora, Condalia hookeri, Xanthoxylum fagara, Celtis pallida, Celtis laevigata, Caesalpinia mexicana, Eysenhardtia polystachya; only few of them are diffuse porous viz., Diospyros palmeri, Diospyros texana. Fibre cell characteristics also showed large variations in morphology, size, lumen breadth and in compactness, these species were soft and hard wood. Most of the species have narrow vessels, viz., Acacia berlandieri, Acacia shaffneri, Acacia wrightii, Helietta parviflora, Cordia boissieri, Diospyros palmeri, Celtis laevigata, Eysenhardtia polystachya, Xanthoxyllum fagara. Celtis pallida contained medium sized vessels, while Celtis laevigata and Caesalpinia mexicana possessed big sized vessels. Many of the species possess narrow vessels which although impose transport of water but protect the vessels against cavitation during drought and freezing the species with small narrow vessels mentioned have strategy to adapt both to hot and cold climate against cavitation. The species having big vessel diameter may be susceptible to drought such as Celtis pallida, Caesalpinia mexicana or they may have deep root system for adaptation to semiarid climates in northeast Mexico. All these wood anatomical traits could be utilized to distinguish species as well as quality determinations of species. The variation in hydraulic systems determine the capacity of water transport among species Statstically significant differences are observed in all wood anatomical parameters among species studied.